2011
DOI: 10.1016/j.bbrc.2011.11.068
|View full text |Cite
|
Sign up to set email alerts
|

Negative-feedback regulation of ATP release: ATP release from cardiomyocytes is strictly regulated during ischemia

Abstract: Extracellular ATP acts as a potent agonist on cardiomyocytes, inducing a broad range of physiological responses via P2 purinoceptors. Its concentration in the interstitial space within the heart is elevated during ischemia or hypoxia due to its release from a number of cell types, including cardiomyocytes. However, the exact mechanism responsible for the release of ATP from cardiomyocytes during ischemia is not known. In this study, we investigated whether and how the release of ATP was strictly regulated duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 26 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…TSC2 ablation in the heart led to not only cardiac dysfunction, but also a decrease in heart rate. ATP is released from cardiomyocytes [ 39 , 40 ] and immediately metabolized to adenosine by ATPases that have their catalytic domain on the outer side of plasma membrane. Since adenosine is known to have a negative effect on heart rate [ 41 ], increased cytosolic ATP level may result in a decrease in heart rate in TSC2 -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…TSC2 ablation in the heart led to not only cardiac dysfunction, but also a decrease in heart rate. ATP is released from cardiomyocytes [ 39 , 40 ] and immediately metabolized to adenosine by ATPases that have their catalytic domain on the outer side of plasma membrane. Since adenosine is known to have a negative effect on heart rate [ 41 ], increased cytosolic ATP level may result in a decrease in heart rate in TSC2 -/- mice.…”
Section: Discussionmentioning
confidence: 99%
“…Others have shown that ischemia is accompanied by an increased release of ATP from cardiac myocytes and sympathetic nerves (Lai and Nishi, 2000;Sesti et al, 2003;Clarke et al, 2009). It has been suggested that release of ATP from cardiomyocytes is strictly regulated during ischemia by a negative feedback mechanism consisting of maxi-anion channel-derived ATP-induced suppression of ATP release via hemichannels in cardiomyocytes (Kunugi et al, 2011). In a recent article (Cosentino et al, 2012), it was shown that ischemic/ hypoxic stress induced rapid ATP release from cultured cardiomyocytes and that distinct P2 receptors regulated cardiomyocyte death, perhaps via P2X 7 and P2Y 2 receptors.…”
Section: Ischemiamentioning
confidence: 99%
“…It has been suggested that release of ATP from cardiomyocytes is strictly regulated during ischaemia by a negative feedback mechanism consisting of maxi-anion channel-derived ATP-induced suppression of ATP release via hemichannels in cardiomyocytes [586]. In a more recent study, it was shown that ischaemic/hypoxic stress induced rapid ATP release from cultured cardiomyocytes and that distinct P2R, perhaps P2X7R and P2Y2R, regulated cardiomyocyte death [587].…”
Section: Ischaemiamentioning
confidence: 99%